Revisiting the metal sites of nitrous oxide reductase in a low-dose structure from Marinobacter nauticus - Pomowski, Anja (2024)
Funding Information: This work was supported by the Deutsche Forschungsgemeinschaft (RTG 1976, Project No. 235777276, and PP 1927, Project No. 311061829 to O.E.) and the European Research Council (Grant No. 310656 to O.E.). The authors thank Lin Zhang for the helpful discussions. Funding Information: Open Access funding enabled and organized by Projekt DEAL. This work was funded by European Molecular Biology Organization, ASTF 282.00-2010, Deutsche Forschungsgemeinschaft, PP 1927, Project No. 311061829, RTG 1976, Project No. 235777276, FP7 Publisher Copyright: © The Author(s) 2024.